The impact of adenomyosis on intrauterine insemination success in unexplained infertile women: a retrospective cross-sectional study - Sefa Arlıer; Sadık Kükrer; Fikriye Işıl Adıgüzel; Ahmet Zeki Nessar; Gülsüm Uysal; Cevdet Adıgüzel; Dilek Kaya Kaplanoğlu (BMC Pregnancy and Childbirth)
Abstract Background Adenomyosis is increasingly recognized as a significant factor affecting fertility, particularly in the context of assisted reproductive technologies (ART). This study aimed to assess the independent impact of adenomyosis on intrauterine insemination (IUI) success rates in women with unexplained infertility. Methods This retrospective cross-sectional study included 533 IUI cycles in 374 infertile women treated at the University of Health Science, assisted reproductive technologies center, Adana City Hospital. The study identified adenomyosis in 95 patients via 2D transvaginal Doppler ultrasonography and 3D transabdominal ultrasonography, whereas direct and indirect adenomyosis features were not detected in 279 patients. Both groups started ovulation induction on cycle day 2–3 using recombinant follicle stimulating hormone (rFSH) or letrozole combined with rFSH or rFSH combined with recombinant luteinizing hormone (rLH). Clinical and ultrasound findings were recorded systematically. IUI was performed 36 h post-human chorionic ggonadotropin (hCG) administration, with pregnancy defined as a positive β-hCG 12–14 days after IUI. Logistic regression models were used to analyze the independent effects of adenomyosis on clinical pregnancy rates, adjusting for potential confounders. Results The cumulative pregnancy rate per cycle was significantly lower in women with adenomyosis (12.23%) compared to those without adenomyosis (20.81%). Adenomyosis was identified as a significant negative predictor of IUI success (OR 0.575, 95% CI: 0.335–0.998, p = 0.049). Conclusion Adenomyosis negatively affects IUI outcomes, suggesting the need for tailored fertility treatment strategies in this population. Routine assessment of adenomyosis should be considered in infertility evaluations to optimize clinical management and treatment success.